Fe incorporated ternary layered double hydroxides with remarkably improved electrochemical performance towards asymmetric supercapacitors. Issue 19 (1st October 2022) - Zhao, Yuanxiang; Feng, Zhihang; Guo, Zengcai; Mu, Jianpeng; Che, Hongwei; Zhang, Zhixiao; Tian, Tian; Xiaoliang, Zhang; Li, Simin; Wang, Yanming; Mu, Jingbo
Abstract: A nanocomposite composed of ternary NiCo2 Fex layered double hydroxide (LDH) anchored to g-C3 N4 was prepared for high-performance supercapacitor. In this novel material, Fe played an important part in enhancing the energy storage performance of the NiCo2 Fex -LDH. Density functional theory calculations on this material showed that Fe improved the Fermi level of NiCo2 Fex -LDH, moreover, the stability of the N–Ni bonds were formed after combining NiCo2 Fex -LDH with g-C3 N4 . The electrochemical test results for this material showed that the NiCo2 Fe1.0 -LDH@g-C3 N4 electrode yielded an extremely high specific capacitance of 1550 F g −1 at a current density of 1 A g −1, which was far superior to that of the NiCo2 -LDH@g-C3 N4 electrode. An assembled NiCo2 Fe1.0 -LDH@g-C3 N4 //AC asymmetric supercapacitor device delivered an impressive specific capacitance of 129.64 F g −1, in addition, the device yielded the energy density of up to 35 Wh kg −1 at the corresponding power density of 701 W kg −1 with superior cycling performance (92.7% capacitance retention after 5000 cycles). The NiCo2 Fe1.0 -LDH@g-C3 N4 //AC asymmetric supercapacitors easily powered a blue LED. The results of this work provide a promising research path for constructing high-performance of NiCo2 -LDH-based nanostructured electrodes materials, which can be employed in new energy storage devices. Graphical abstract: Image 1